THE INFLUENCE OF WORK DISCIPLINE AND RECRUITMENT ON EMPLOYEE PERFORMANCE AT PT. KARINDO SAKTI SOURCES THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE (At PT. Sumber Karindo Sakti) - Yessica Sardina Purba (PT. Radja Intercontinental Publishing, 2024)
Based on the results of the analysis of hypothesis 1, it can be seen thatWork discipline influences job satisfaction. The results of this research are in accordance with the results of research conducted by (Nugrahaningsih & Julaela, 2022) showing that work discipline has a significant effect on job satisfaction. Based on the results of respondents' answers to the three statements contained in the research questionnaire regarding work discipline, the average respondent tended to agree and strongly agree. Where in the statement employees have awareness in carrying out company duties and regulations both in attendance and using company equipment properly. This indicates a high level of good discipline, such as employees having awareness in carrying out their work and complying with company regulations, which can influence the job satisfaction of PT employees. Source Karindo Sakti. According to(Hasibuan, 2016) that work discipline has a direct influence on employee job satisfaction, so discipline is an important factor in a company. This is considered an important factor because work discipline can influence employee job satisfaction. The higher the employee's work discipline, the higher the employee's job satisfaction. Then we also looked at the characteristics of the respondents based on age, where the majority of respondents were aged 25-35 years. This is because this age is the productive age at work. So it can be said that employees who work in the production section of PT Sumber Karindo Sakti get satisfaction at work.